Enterobacter cloacae complex outbreak in a neonatal intensive care unit: multifaceted investigations and preventive measures are needed. (October 2021) - Rahal, A.; Andreo, A.; Le Gallou, F.; Bourigault, C.; Bouchand, C.; Ferriot, C.; Corvec, S.; Guillouzouic, A.; Gras-Leguen, C.; Launay, E.; Flamant, C.; Lepelletier, D.
Summary: We report the investigation to control an Enterobacter cloacae complex outbreak in a neonatal intensive care unit from November 2020 to February 2021. Pulsed-field gel electrophoresis showed that five of eight cases were infected with a clonal strain. Breast pumps, shared among mothers in the unit, could have contributed to the spread of the clonal spread.